Impact of Glucose Exposure on Outcomes of a Nation-Wide Peritoneal Dialysis Cohort – Results of the BRAZPD II Cohort - Radunz, Vitor; Pecoits-Filho, Roberto; Figueiredo, Ana Elizabeth; Barretti, Pasqual; de Moraes, Thyago Proença (Frontiers in Physiology, 2019)
Background: Data investigating the association of glucose exposure with technique failure and patient survival are limited to retrospective cohorts and was never tested outside Asia and considering the presence of competing risks. Method: Prospective multicenter cohort study of incident peritoneal dialysis patients where the association of cumulative glucose exposure in 6,12 and 24 months with patient survival and technique failure was tested using Cox regression analysis and competing risk analysis. Results: We analyzed 4367 incident peritoneal dialysis patients with mean age 59.0±15.8 years, 43.9% were diabetics, 46.7% males and 64.4% Caucasians. Glucose exposure was not associated with patient survival independent of the time of exposure and even after adjustments for confounders. In contrast, higher glucose exposure was associated with more technique failure in the Cox and competing risk models. The higher risk for technique failure was found in the subgroup exposed to the higher amount of glucose to a maximum of 86% in the model analyzing cumulative glucose exposure for 1 year. Conclusion: Glucose exposure was associated with technique failure but not with patient survival.